Analisis Waste pada Unit Crushing Plant di PT Silva Andia Utama - Agung Sudarmaji; Muhardi; Eka Tresna Gumelar (UNISBA Press, 2023)
Abstract. PT. Silva Andia Utama is an andesite mining company. The company in its production never reaches the target set by the company. The unachieved production target is indicated as a result of a process that generates a lot of waste. This research will focus on identifying any waste that appears in the crushing plant unit of PT. Silva Andia Utama. The study was started by observing for 30 working days. Based on the observation results, there are 5 types of waste that appear, namely overproduction, inventory, motion, process, and waiting waste. Waste waiting is the most dominant waste with a value of 28.8%. Abstrak. PT Silva Andia Utama adalah perusahaan pertambangan batu andesit. Perusahaan dalam produksinya tidak pernah mencapai target yang ditetapkan oleh perusahaan. Ketidaktercapaian target produksi ini diindikasi akibat dari proses yang banyak menimbulkan waste. Penelitian ini akan berfokus pada pengidentifikasian waste apa saja yang muncul pada unit crushing plant PT. Silva Andia Utama. Penelitian dimulai dengan melakukan observasi selam 30 hari kerja. Berdasarkan hasil observasi terdapat 5 jenis waste yang muncul yakni waste overproduction, inventory, motion, process, dan waiting. Waste waiting merupakan waste yang paling dominan dengan nilai 28.8 %.